Genome-wide 5-hydroxymethylcytosine (5hmC) reassigned in Pten-depleted mESCs along neural differentiation - Wang, Zhangting; Miu, Kai-Kei; Chan, See-Wing; Ou, Fanghong; Wai-Nok Law, Patrick; Chan, Wai-Yee (Frontiers in Cell and Developmental Biology, 2022)
DNA methylation and hydroxymethylation have been implicated dynamic in normal development and differentiation. 5-hydroxymethylcytosine (5hmC), created by the ten eleven translocation (TET) proteins-catalyzed oxidation of 5-methylcytosine (5mC), is most abundant in the brain, but the genome-wide distribution of 5hmC during diverse neuronal differentiation remains unknown. Here, we used an in vitro model to differentiate mouse embryonic stem cells (ESCs) into ventral midbrain and hindbrain neural progenitors and characterized the global 5hmC distribution using nano-5hmC-seal approach. The 5hmC pattern was dynamic in promoters, exons and enhancers, associated with gene activation and repression. For example, ventral midbrain marker (Lmx1a, Otx2, Th) and hindbrain marker (Hoxa1, Zic1, Tph1) acquire 5hmC and were upregulated during differentiation. Among the differentially expressed genes involved in both midbrain and hindbrain lineage commitment, phosphatase and tensin homolog (Pten) was identified as a key regulator for neuronal development. We found that Pten knockout disrupted the normal differentiation of midbrain/hindbrain neural progenitors, resulted in immature neurons. In addition, 4111 and 203 differentially hydroxymethylated regions (DhMRs) were identified in the differentiation of Pten-/- mESC into ventral midbrain and hindbrain progenitors, respectively. Gene ontology analysis showed that the majority of these DhMRs were associated with neurogenesis, ectoderm development and signal transduction. Moreover, further combinational analysis of 5hmC pattern and transcriptomic profile in the midbrain progenitor cells demonstrated Pten as a functional factor to modulate mitochondrial associated pathways. Therefore, our findings elucidated the molecular mechanisms underlying lineage-specific differentiation of pluripotent stem cells to the midbrain/hindbrain progenitors. In addition, Pten was also identified as a key regulator for the midbrain/hindbrain development.